Effect of Prooxidative Natural Products: Comparison of the OSI1 (YKL071w) Promoter Luciferase Construct from Yeast with an Nrf2/Keap Reporter System - Ivan Schlembach; Andreas Uebachs; Tim Caspers; Athanassios Fragoulis; Alan J. Slusarenko; Martin C. H. Gruhlke (Applied Sciences, 2020)
The oxidative stress response (OSR) in yeast is under the control of oxidation-sensitive cysteines in the Yap1p transcription factor, and fusion of the Yap1p-dependent OS-induced promoter of the YKL071w gene (OSI1) to a luciferase coding sequence makes a sensitive reporter for OS induced by electrophiles. In mammalian cells, the OSR induced by electrophiles is coordinated in a mechanistically similar way via oxidation-sensitive cysteines in the kelch-like ECH-associated protein 1 (Keap1)– nuclear factor erythroid 2-related factor 2 / antioxidant response element ( Nrf2/ARE) system. Many electrophilic oxidants have already been independently shown to trigger both the Yap1 and Keap1 systems. Here, we investigated the responses of Yap1 and Keap1 reporters to sulforaphane (SFN), allyl isothiocyanate (AITC), phenylethyl isothiocyanate (PEITC), previously known to stimulate Keap1–Nrf2/ARE but not known to activate Yap1, and as a positive control, allicin, previously reported to stimulate both Yap1 and Nrf2. We have compared the reciprocal responsiveness of the respective reporter systems and show that the yeast reporter system can have predictive value for electrophiles that stimulate the mammalian Keap1–Nrf2/ARE system.